Mitochondrial Functions in Infection and Immunity - Tiku, Varnesh; Tan, Man-Wah; Dikic, Ivan (Trends in cell biology, 2020)
Mitochondria have a central role in regulating a range of cellular activities and host responses upon bacterial infection. Multiple pathogens affect mitochondria dynamics and functions to influence their intracellular survival or evade host immunity. On the other side, major host responses elicited against infections are directly dependent on mitochondrial functions, thus placing mitochondria centrally in maintaining homeostasis upon infection. In this review, we summarize how different bacteria and viruses impact morphological and functional changes in host mitochondria and how this manipulation can influence microbial pathogenesis as well as the host cell metabolism and immune responses. Bacteria and viruses have evolved specific ways of targeting mitochondria to perturb mitochondrial function that can prove to be beneficial for these microbes.Many bacteria and viruses use specific virulence mechanisms to modulate mitochondrial dynamics, leading to either mitochondrial fusion or fission.Mitochondrial metabolism can also be impacted by bacterial and viral infections.While in some cases bacteria and viruses induce the mitochondrial cell death pathway, in others cell death is inhibited promoting intracellular bacterial and viral proliferation.Mitochondria regulate different innate immune signaling pathways induced upon bacterial or viral infections.